ChemInform Abstract: Nanocomposites of Graphene/Polymers: A Review. Issue 42 (October 2015) - Chee, W. K.; Lim, H. N.; Huang, N. M.; Harrison, I.
Abstract Review: fabrication, properties and practical applications; 176 refs.